Peristiwa Intifadah dalam Cerpen Li Man Nahmil Al-Rasas Karya Jihad Al-Rajbi - Reni Ilmayanti (Alfaz (Arabic Literatures for Academic Zealots), 2018)
This paper examines a collection of short stories entitled: Liman nahmil al-Rasasah by Jihad Al-Rajbi>using the semiotic approach of Charles Sander Peirce. This paper intends to describe the symbolic meaning implicit in the text in expressing the reality of the events behind the Intifada in the Palestinian state presented in the short stories of Jihad Al-Rajbi. This research includes library research; by reviewing library materials, in the form of books, encyclopedias, journals and other sources relevant to the topic being studied. The results of the analysis found that the language used by the author in conveying communication to the public was a symbolic language, to deliver the reader to the context of the Palestinian people in the period 1967-1993. Bullet words (Al-Rasasah), small stone stones, children, mothers, al-Quds, seclusion is a symbol that is often repeated in short story narratives. This symbolizes the oppression of the Palestinian people over Israeli cruelty, so the word used as the parent title of the collection of short stories Intifadhah is the word bullet (Al-Rasasah).